1992
DOI: 10.2307/2154055
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Periodic Orbits of Maps of the Interval

Abstract: Abstract.Let n and 6 be cyclic permutations of finite ordered sets. We say that n forces 6 if every continuous map of the interval which has a representative of n also has one of 6 . We give a geometric version of Jungreis' combinatorial algorithm for deciding in certain cases whether n forces 9 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Then one obtains a transitive relation → on C. The relation → is a refinement of the Sharkovskiȋ ordering , which has been studied by many authors (see [1,2,3,4,5,6,7,8,9,10,12,23,24], etc.). In the following we will also study this relation.…”
Section: Some Results On Periodic Patternsmentioning
confidence: 99%
“…Then one obtains a transitive relation → on C. The relation → is a refinement of the Sharkovskiȋ ordering , which has been studied by many authors (see [1,2,3,4,5,6,7,8,9,10,12,23,24], etc.). In the following we will also study this relation.…”
Section: Some Results On Periodic Patternsmentioning
confidence: 99%
“…Jungreis [6] provided a combinatorial method to determine if one cycle forces another in certain cases. In [3] a geometric version of Jungreis's algorithm is given and in [4] this algorithm is generalized to any two cycles. In [8], another geometric algorithm is given to determine the forcing relation.…”
Section: Definitions Throughout This Note F : I → I Denotes a Contimentioning
confidence: 99%
“…In [3] it is shown that if α is a double then at least one element of I(α) is a representative of α/2 -namely, the tightest. Given the construction of I(α), it is clear that at most one element of I(α) can be a representative of α/2.…”
Section: Lemma 5 If X Is In the K Th Lap Of H J Then The First J Tmentioning
confidence: 99%